Beauty in the eyes of Adam a cultivation analysis on adolescent boys' views of beauty - Reyes, Abigail Carpiz 1993-; Avecilla, Victor C.; University of the Philippines. College of Mass Communication (2014)
"For this study, Susannah Stern's "All I Really Needed to Know (About Beauty) I Learned in Kindergarten" is replicated to see if the results apply in the Filipino setting, involving adolescent boys as participants. The research determines how television viewing shapes adolescent boys' perceptions of beauty through beauty advertisements using the Cultivation Analysis Theory by George Gerbner. To explore the differences in the perceptions of beauty between light and heavy viewers, the study analyzes the relationship of adolescent boys amount of television viewing and their thought about beauty as well as the viewing habits of the respondents. From the data gathered through eight semi-structured interviews with adolescent boys, there were no distinct differences with how light and heavy viewers defined beauty. The biggest factor that contributed to this blurry distinction was the difficulty in isolating information from television alone with the onset of modern technologies today. However, the influence of television to adolescent boys is still huge, which resulted to formulaic representations of beauty that were evident in how they described and defined beauty."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Television and teenagers -- Philippines; Teenage boys -- Attitudes; Beauty, Personal -- Public opinion